Time evolution of a small reactive system - Badiali, J.P. (Condensed Matter Physics, 2013)
We investigate the irreversible evolution of a small system in which a chemical reaction takes place. We have two main goals: the first requires to find an equation to produce a time-irreversible behavior,the second consists in introducing a simple exactly solvable model in order to understand basic facts in chemical kinetics. Our basic tool is the transition function counting the number of paths joining two points in the reactive coordinates system. An exact quantum Smoluchowski equation is derived for the reactive system in vacuum, in presence of a solvent in equilibrium at any time with the reactive system a new Smoluchowski equation is obtained. The transition from a quantum regime to a classical one is discussed. The case of a reactive system not in equilibrium with its neighborhood is investigated in terms of path integral and via a partial differential function. Memory effects and closure assumptions are discussed. Using a simple potential model the chemical rate constant is calculated exactly and questions such as the meaning of the activation energy or the physical content of the so-called prefactor are investigated. Ми дослiджуємо незворотну еволюцiю невеликих систем, у яких вiдбувається хiмiчна реакцiя. Ми ставимо подвiйну мету: перша вимагає знаходження рiвняння, яке задає часово-зворотню поведiнку, друга полягає у побудовi моделi з можливим точним розв’язком, щоб зрозумiти основнi подiї хiмiчної кiнетики.
Нашим головним знаряддям є функцiя переходу, яка обчислює кiлькiсть шляхiв, що з’єднують двi точки у системi координат реакцiї. Розвинуто точне квантове рiвняння Смолуховського для системи з реакцiєю у вакуумi. У випадку присутностi розчинника, що перебуває у будь-який момент часу у рiвновазi iз системою з реакцiєю, побудовано нове рiвняння типу Смолуховського. Обговорено перехiд вiд квантової поведiнки до класичної. Також обговорено випадок системи з реакцiєю, яка не перебуває у рiвновазi з оточенням; вiн дослiджується з використанням iнтегралiв за траєкторiями i диференцiальних рiвнянь у частинних похiдних. Вивчено ефекти пам’ятi та умови замикання. Для простої моделi взаємодiї точно розрахована константа реакцiї, a також обговорено, яке значення має енергiя активацiї i фiзичний змiст множника перед експонентою.